Emission-induced nonlinearities in the global aerosol system: Results from the ECHAM5-HAM aerosol-climate model - Stier, P; Feichter, J; Kloster, S; Vignati, E; Wilson, J (2006)
In a series of simulations with the global ECHAM5-HAM aerosol-climate model, the response to changes in anthropogenic emissions is analyzed. Traditionally, additivity is assumed in the assessment of the aerosol climate impact, as the underlying bulk aerosol models are largely constrained to linearity. The microphysical aerosol module HAM establishes degrees of freedom for nonlinear responses of the aerosol system. In this study's results, aerosol column mass burdens respond nonlinearly to changes in anthropogenic emissions, manifested in alterations of the aerosol lifetimes. Specific emission changes induce modifications of aerosol cycles with unaltered emissions, indicating a microphysical coupling of the aerosol cycles. Anthropogenic carbonaceous emissions disproportionately contribute to the accumulation mode numbers close to the source regions. In contrast, anthropogenic sulfuric emissions less than proportionally contribute to the accumulation mode numbers close to the source regions and disproportionately contribute in remote regions. The additivity of the aerosol system is analyzed by comparing the changes from a simulation with emission changes for several compounds with the sum of changes of single simulations, in each of which one of the emission changes was introduced. Close to the anthropogenic source regions, deviations from additivity are found at up to 30% and 15% for the accumulation mode number burden and aerosol optical thickness, respectively. These results challenge the traditional approach of assessing the climate impact of aerosols separately for each component and demand for integrated assessments and emission strategies. © 2006 American Meteorological Society.